Pharmacogenomics in colorectal cancer: A genome-wide association study to predict toxicity after 5-fluorouracil or FOLFOX administration - Fernandez-Rozadilla, C; Cazier, J; Moreno, V; Crous-Bou, M; Guinó, E; Durán, G; Lamas, M; López, R; Candamio, S; Gallardo, E; Paré, L; Baiget, M; et al. (2013)
The development of genotyping technologies has allowed for wider screening for inherited causes of variable outcomes following drug administration. We have performed a genome-wide association study (GWAS) on 221 colorectal cancer (CRC) patients that had been treated with 5-fluorouracil (5-FU), either alone or in combination with oxaliplatin (FOLFOX). A validation set of 791 patients was also studied. Seven SNPs (rs16857540, rs2465403, rs10876844, rs10784749, rs17626122, rs7325568 and rs4243761) showed evidence of association (pooled P-values 0.020, 9.426E-03, 0.010, 0.017, 0.042, 2.302E-04, 2.803E-03) with adverse drug reactions (ADRs). This is the first study to explore the genetic basis of inter-individual variation in toxicity responses to the administration of 5-FU or FOLFOX in CRC patients on a genome-wide scale. © 2013 Macmillan Publishers Limited. All rights reserved 1470-269X/13.